TRANSFORMASI KAMPUNG PANCASILA: PENDAMPINGAN DIGITALISASI UNTUK MENINGKATKAN KINERJA PEMERINTAHAN DESA NONGKODONO - Muhamad Fajar Pramono; Aziz Musthafa; Dian Afif Arifah; Aldy Alfajri (Jurnal Terapan Abdimas, 2025)
Abstract. This community service initiative intends to improve the digital governance performance of Nongkodono Village, the first Kampung Pancasila in Ponorogo, East Java. While Kampung Pancasila programs in Indonesia frequently emphasize symbolic and formalistic approaches, this project aims to provide a functional, quantifiable, and progressive framework in line with Nongkodono's 2022 Medium-Term Village Development Plan (RPJMDes). The first-year program aims to improve village governance by implementing digital solutions, including the Smart Government system. This system was developed by integrating online administrative services based on citizen data with digital asset management to facilitate reporting to local government. This effort was carried out through collaboration with stakeholders, comparative studies with similar communities, and extensive training sessions. The results include the development of a functional Smart Government application and skill capacity improvement among village officials to use digital technologies for governance. Beyond immediate efficiency gains, this effort aims to promote widespread adoption of digital government in rural areas, establishing a national standard for Kampung Pancasilas. The Smart Government digital system becomes the main output in this program. The results of this program are also published in the mass media, online news, and accredited scientific journals to broaden insight into Pancasila's values ??and the potential of a digital revolution in empowering society.   Abstrak. Program pengabdian masyarakat ini bertujuan untuk meningkatkan kinerja pemerintahan Desa Nongkodono melalui penerapan sistem digital. Sebagai Kampung Pancasila pertama di Ponorogo, Jawa Timur, program ini tidak hanya berfokus pada simbolisme tetapi juga mengembangkan pendekatan yang lebih fungsional, terukur, dan progresif sesuai dengan Rencana Pembangunan Jangka Menengah Desa (RPJMDes) tahun 2022. Pada tahun pertama, program ini memprioritaskan penerapan sistem Smart Government yang dirancang untuk mengintegrasikan layanan administrasi berbasis data warga dan manajemen aset digital, guna meningkatkan efisiensi pelaporan dan pelayanan desa. Kegiatan ini melibatkan kolaborasi dengan berbagai pemangku kepentingan, studi banding dengan desa lain yang telah menerapkan konsep serupa, serta pelatihan untuk meningkatkan kapasitas perangkat desa dalam memanfaatkan teknologi digital. Hasil yang dicapai meliputi pengembangan aplikasi Smart Government yang fungsional dan peningkatan keterampilan aparatur desa. Program ini juga diharapkan mendorong penerapan luas sistem pemerintahan digital di desa-desa lain, sekaligus memperkuat nilai-nilai Pancasila melalui tata kelola yang inovatif. Publikasi hasil program dilakukan melalui media massa, berita daring, dan jurnal ilmiah untuk memperluas wawasan tentang pentingnya transformasi digital dalam pemberdayaan masyarakat dan pengelolaan pemerintahan desa.